A parabolic trough solar collector as a solar system for heating water: a study based on numerical simulation - Mokhtar Ghodbane (International Journal of Energetica)
This paper is an optical and thermal study of a small model of a parabolic trough solar collector (CTP), which will be used to heat tap water in the winter at Guemar, El-Oued province, Algeria. A mathematical model drawn from the energy balance equation applied to the absorber tube, this model was solved by the finite difference method. A computer program was developed to solve our problem. MATLAB was used as a tool for numerical simulation where it is used to calculate dynamic shifts at the level of the absorbent tube. The results are very honorable and encouraging, where the thermal efficiency of the concentrator had passed 61%, and the fluid temperature had passed 343 K.